IMPLEMENTASI SISTEM BAGI HASIL DALAM PENGELOLAAN PARKIR DI PASAR TRADISIONAL MUARA SABAK BARAT: PERSPEKTIF HUKUM ISLAM - Triwidodo, Abdullah; Musthofa, M. Arif; Wulandari, Triyana (Universitas Islam Sumatera Utara, 2025)
The parking management system at Muara Sabak Barat Traditional Market applies a profit-sharing scheme between the parking operators and the local government. This study aims to analyze the compatibility of this system with Islamic economic concepts, particularly mudharabah and musyarakah, and to evaluate its impact on the local economy. A qualitative approach was employed using observation, interviews, and document analysis. The findings indicate that the profit-sharing system bears similarities to Islamic economic principles but does not fully reflect the values of justice and balance. The profit distribution tends to favor the local government, while the responsibility for losses is not proportionally shared. Moreover, transparency in the management of parking funds remains inadequate. From a local economic perspective, the system contributes to job creation for parking attendants but has not significantly improved the income of market traders. This study recommends enhancing transparency in parking revenue reporting, implementing stricter supervision to prevent fund leakage, and revising the profit-sharing scheme to ensure a fairer distribution among stakeholders. Digitalization in parking monitoring is also suggested as a solution to improve accountability. With these improvements, traditional market parking management is expected to become more efficient, transparent, and sustainable in accordance with Islamic economic principles.